The Burden of Disease due to COVID-19 in Korea Using Disability-Adjusted Life Years - Jo, Min-Woo; Go, Dun-Sol; Kim, Rhieun; Lee, Seung Won; Ock, Minsu; Kim, Young-Eun; Oh, In-Hwan; Yoon, Seok-Jun; Park, Hyesook (Journal of Korean medical science, 2020)
The world is currently experiencing a pandemic of coronavirus disease 2019 (COVID-19). In Korea, as in other countries, the number of confirmed cases and deaths due to COVID-19 have been rising. This study aimed to calculate the burden of disease due to COVID-19 in Korea. We used data on confirmed cases and deaths due to COVID-19 between January 20 and April 24, 2020 provided by the Korea Centers for Disease Control and Prevention, the local governments and the public media to determine disability-adjusted life years (DALYs) by sex and age. Morbidity was estimated directly among the confirmed, cured, and fatal cases. Disability weights were adopted from previous similar causes on the severity of COVID-19 for the years of life lived with disability (YLDs). The years of life lost (YLLs) were calculated using the standard life expectancy from the 2018 life tables for each sex and age. The YLDs were higher in females (155.2) than in males (105.1), but the YLLs were higher in males (1,274.3) than in females (996.4). The total disease burden attributable to COVID-19 in Korea during the study period, was estimated to be 2,531.0 DALYs, and 4.930 DALYs per 100,000 population. The YLDs and the YLLs constituted 10.3% and 89.7% of the total DALYs, respectively. The DALYs per 100,000 population were highest in people aged ≥ 80 years, followed by those aged 70-79, 60-69, and 50-59 years, but the incidence was the highest in individuals aged 20-29 years. This study provided the estimates of DALYs due to COVID-19 in Korea. Most of the disease burden from COVID-19 was derived from YLL; this indicates that decision-makers should focus and make an effort on reducing fatality for preparing the second wave of COVID-19.